Kerangka Kerja CER sebagai Upaya untuk Membantu Mahasiswa Tahun Pertama dalam Menulis Argumen Ilmiah - Priyanto, Priyanto; Ningsih, Arum Gati; Nurfadilah, Nurfadilah (Program Studi Pendidikan Bahasa dan Sastra Fakultas Keguruan dan Ilmu Pendidikan Universitas Jambi, 2024)
Writing scientific arguments is an essential skill in higher education, yet first-year students often face difficulties in constructing systematic and evidence-based arguments. This study aims to analyze the application of the Claim, Evidence, Reasoning (CER) framework in learning to write scientific arguments in higher education. Using a descriptive qualitative approach, this study involved first-year students in a series of learning activities to write scientific arguments using the CER framework. Data were collected through analyzing students' argument texts and classroom observations. The results showed that the CER framework helped students to develop claims that were more specific and based on real problems. In addition, students are also able to select and cite relevant evidence from trusted sources, and develop logical reasoning in linking evidence to claims. However, there are still challenges in finding and evaluating the credibility of sources, as well as in constructing explicit reasoning. Therefore, learning reinforcement strategies, such as interactive discussions, independent practice, guidance in finding credible sources, and individualized feedback are needed to increase the effectiveness of the CER framework in learning academic writing. This study confirms that the CER framework is an effective approach to improve students' critical thinking and academic writing skills.